Co-Delivery of M2e Virus-Like Particles with Influenza Split Vaccine to the Skin Using Microneedles Enhances the Efficacy of Cross Protection - Min-Chul Kim; Ki-Hye Kim; Jeong Woo Lee; Yu-Na Lee; Hyo-Jick Choi; Yu-Jin Jung; Yu-Jin Kim; Richard W. Compans; Mark R. Prausnitz; Sang-Moo Kang (MDPI AG, 2019)
It is a high priority to develop a simple and effective delivery method for a cross-protective influenza vaccine. We investigated skin immunization by microneedle (MN) patch with human influenza split vaccine and virus-like particles containing heterologous M2 extracellular (M2e) domains (M2e5x virus-like particles (VLP)) as a cross-protective influenza vaccine candidate. Co-delivery of influenza split vaccine and M2e5x VLP to the skin by MN patch was found to confer effective protection against heterosubtypic influenza virus by preventing weight loss and reducing lung viral loads. Compared to intramuscular immunization, MN-based delivery of combined split vaccine and M2e5x VLPs shaped cellular immune responses toward T helper type 1 responses increasing IgG2a isotype antibodies as well as IFN-γ producing cells in mucosal and systemic sites. This study provides evidence that potential immunological and logistic benefits of M2e5x VLP with human influenza split vaccine delivered by MN patch can be used to develop an easy-to-administer cross-protective influenza vaccine.